Demystifying Shamans and Their World A Multidisciplinary Study. - Rock, Adam J.; Krippner, Stanley (Luton : Andrews UK, 2011)
Shamanism can be described as a group of techniques by which its practitioners enter the "spirit world," purportedly obtaining information that is used to help and to heal members of their social group. Despite a resurgence of interest in shamanism and shamanic states of consciousness, these phenomena are neither well-defined nor sufficiently understood. This multi-disciplinary study draws on the fields of psychology, philosophy and anthropology with the aim of demystifying shamanism. The au...
Chapter Five: Applying a 10-Facet Model to North and South American Shamanic Dream SystemsChapter Six: The Construction of an Ontology and Epistemology of Shamanic Journeying Imagery; Chapter Seven: Necessary Conditions For Shamanic Journeying Imagery; Chapter Eight: The Issue of Realism and Shamanic Journeying Imagery; Chapter Nine: Methods for Studying Shamanic Reports of Psychic Phenomena; Chapter Ten: Shamanism and the Demystification Journey; Back Matter; References; Also Available
Description based upon print version of record.
Keywords: Shamanism; Shamans; BODY, MIND & SPIRIT / Spirituality / Shamanism; Electronic books